Deployment challenges of MIPV6 - Masud, Mosharrof Hussain; Anwar, Farhat (IIUM Press, 2011)
PDA). laptop. notebook. digital camera. microwave woven, refrigerator, security sensors,car. webcam. washing machine, television. toaster etc. are facilitated with the Internet connection. To connect all these devices with the Internet. Internet Protocol version 4 (lPv4) was designed in 1970 [I].When IPv4 was designed, mobility of a device did not consider for its gigantic size. However, as the technology advances, electronic devices become smaller and portable. Among these devices. the mobile handsets arc increasing rapidly anlund the world. Mobile users demand not only better Quality of Services (QoS) but also seamless and uninterrupted communication. To provide satisfactory services to the mobile users, Internet Engineers Task Force (lETF) has been developed Mobile Internet Protocol (~1IP) protocol [2]. MIP can be categorized into two paI1s. the existing MIP version 4 (~1IPv4) and coming MIPv6. MIPv4 was developed during 1993 to 1998 [3]. The address length ofIPv4 is 32 bits (2'2) that has around 4 billion address spaces. In figure 13.1 [4]. it depicts that IPv4 can only accommodate 4 billion of users where the current population of the world is around 7 billion and it is increasing linearly